Kejohanan karnival sukan staf UiTM Cawangan Selangor (KASSUS) 2023 / Fairos Abdul Hamid and Zakiah Mohd Noordin - Abdul Hamid, Fairos; Mohd Noordin, Zakiah (Faculty of Pharmacy, 2023)
The UiTM Selangor Staff Sports Carnival 2023 (Kejohanan Karnival Sukan Staf Uitm Cawangan Selangor) was conducted on 11th to 26th February 2023 at UiTM Puncak Alam campus. Organised by the Sports Unit, UiTM Selangor branch, the tournament was participated by more than 1000 staffs from five uitm campuses namely UiTM Puncak Alam, Puncak Perdana, Dengkil, Selayang and Sungai Buloh. On this occasion, the Faculty of Pharmacy has sent a total of 32 staff to compete in 5 sports, including volleyball, netball, badminton, table tennis and petanque.